(untitled) (UUM Journal of Legal Studies, 2021)
Immunisation protection includes vaccination programme that is very crucial to prevent the spread of disease among children or those with low immune systems. However, the cases of contagious diseases such as measles have increased dramatically in many countries around the world, including Malaysia. This may be partly due to the rise of certain groups or movements that do not believe in the efficacy of the vaccines. This paper outlined the scenario and existing framework on the administration of the vaccines in Malaysia, with respect to the practices of some countries namely the United State, Italy and Singapore on the implementation of the immunisation programme to its community. Subsequently, this paper highlighted the issues on compulsory vaccination on whether it violated the fundamental liberties incorporated in the Federal Constitution. The researchers adopted a doctrinal approach, whereby materials were compiled from the Malaysian and other jurisdictions’ legislations, case laws, journal articles, and databases. This paper is intended for policymakers as well as the public to understand the possibility for implementing compulsory vaccinations from a legal perspective.